Psychological responses and factors associated with depression and anxiety in entry personnel under quarantine during pandemic in China - Liping Chen; Qiao Chu; Chenhui Xu; Feng Zhou; Xiaolong Hu; Zhaoxin Wang; Ying Jin; Yipeng Lv; Yipeng Lv (Frontiers Media S.A., 2024)
BackgroundThe global COVID-19 pandemic has highlighted critical concerns surrounding mental health. Social isolation measures, such as the quarantine of incoming travelers, are essential public health strategies for the prevention and control of infectious diseases. However, quarantine can lead to adverse psychological outcomes, including feelings of confinement, boredom, perceived scarcity of supplies and information, financial hardship, and social stigma. This study aims to assess the mental states of quarantined individuals, investigate the factors affecting their mental well-being, and examine their coping mechanisms, with the objective of providing recommendations to enhance mental health in anticipation of future outbreaks, such as Disease X.MethodsWe surveyed 327 individuals in quarantine from September 22, 2020 to January 9, 2021, collecting general demographic data and information related to COVID-19. Depression and anxiety were assessed using the PHQ-9 and GAD-7 scales, respectively, while stress coping was evaluated with a simplified version of the Cope scale. We analyzed the relationships between independent variables and mental health outcomes.ResultsAmong the individuals undergoing entry quarantine, 27.8% reported symptoms of depression, and 20.5% reported symptoms of anxiety. Students were more likely to experience depression compared to those with permanent jobs or no occupation. Significant risk factors for both depression and anxiety included pre-existing health conditions, lack of medical insurance, concerns about shortages of daily necessities during quarantine, and high scores for "guilt and self-blame." Additionally, participants who worried about the impact of the epidemic on their studies or work, and those with high scores for "denial," were more likely to exhibit depressive symptoms. On the other hand, participants who were concerned about potential rejection or discrimination from the outside world after quarantine were more prone to anxiety symptoms.ConclusionAttention should be paid to the negative psychological reactions of the entry quarantined personnel, especially those with pre-existing health conditions, those without medical insurance, and students studying abroad. Accurate and effective epidemic dynamic information and preventive and control measures can be provided to the public to prevent fear and stigma against quarantined personnel.